2012
DOI: 10.1038/nature11421
|View full text |Cite
|
Sign up to set email alerts
|

A 61-million-person experiment in social influence and political mobilization

Abstract: Human behaviour is thought to spread through face-to-face social networks, but it is difficult to identify social influence effects in observational studies9–13, and it is unknown whether online social networks operate in the same way14–19. Here we report results from a randomized controlled trial of political mobilization messages delivered to 61 million Facebook users during the 2010 US congressional elections. The results show that the messages directly influenced political self-expression, information seek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
1,289
2
52

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,954 publications
(1,446 citation statements)
references
References 29 publications
31
1,289
2
52
Order By: Relevance
“…This is just one example of the uncharted territory that societies are now trying to navigate. Similar questions can be asked about Facebook's documented power to affect its users' moods (Kramer, Guillory, and Hancock 2014) and to influence their voting behaviour (Bond et al 2012).…”
Section: Corporate Powermentioning
confidence: 99%
“…This is just one example of the uncharted territory that societies are now trying to navigate. Similar questions can be asked about Facebook's documented power to affect its users' moods (Kramer, Guillory, and Hancock 2014) and to influence their voting behaviour (Bond et al 2012).…”
Section: Corporate Powermentioning
confidence: 99%
“…Polling evidence suggests that voters, and particularly young voters, do not trust parties or media organizations, but they are more likely to be influenced by the attitudes and behavior of those in their peer groups. Scientific studies have also indicated that this kind of "targeted sharing" through Facebook can have a small but significant impact on voting, especially among the 18-29 age group (Bond et al 2012). …”
Section: Social Media the Social Graph And Targeted Sharingmentioning
confidence: 99%
“…To the extent experimental research has attempted to identify the effect of internet advertising on the public's perceptions, beliefs, evaluations, or 'offline' behavior, subjects are typically aware that they are being studied, having been previously enrolled in a research study or asked to browse the internet while sitting in a researcher's lab (e.g., Danaher and Mullarkey 2003;Buscher et al 2009;Grimmer et al 2012). One of the few unobtrusive studies finds that online ads boost in-store purchases among pre-existing customers , 2 and the sole study to examine offline political outcomes finds that Facebook's reminders to vote nudge turnout upward, but only when accompanied by pictures of friends (Bond et al 2012).…”
mentioning
confidence: 99%